Perturbing local steroidogenesis to improve breast cancer immunity - Qiuchen Zhao; Jhuma Pramanik; Yongjin Lu; Natalie Z. M. Homer; Charlotte J. Imianowski; Baojie Zhang; Muhammad Iqbal; Sanu Korumadathil Shaji; Andrew Conway Morris; Rahul Roychoudhuri; Klaus Okkenhaug; Pengfei Qiu; et al. (Nature Communications)
Abstract Breast cancer, particularly triple-negative breast cancer (TNBC), evades the body’s immune defences, in part by cultivating an immunosuppressive tumour microenvironment. Here, we show that suppressing local steroidogenesis can augment anti-tumour immunity against TNBC. Through targeted metabolomics of steroids coupled with immunohistochemistry, we profiled the existence of immunosuppressive steroids in TNBC patient tumours and discerned the steroidogenic activity in immune-infiltrating regions. In mouse, genetic inhibition of immune cell steroidogenesis restricted TNBC tumour progression with a significant reduction in immunosuppressive components such as tumour associated macrophages. Steroidogenesis inhibition appears to bolster anti-tumour immune responses in dendritic and T cells by impeding glucocorticoid signalling. Undertaking metabolic modelling of the single-cell transcriptomics and targeted tumour-steroidomics, we pinpointed the predominant steroidogenic cells. Inhibiting steroidogenesis pharmacologically using a identified drug, posaconazole, curtailed tumour expansion in a humanised TNBC mouse model. This investigation paves the way for targeting steroidogenesis and its signalling pathways in breast cancer affected by immune-steroid maladaptation.